Intrinsic and extrinsic factors contributing to the Success of Javanese Food Entrepreneurs in Kota Kinabalu, Sabah - Syahrul Nizam Salam; Jasman Bandar; Suddin Lada; Ghazali Hassan; Joehan Joehari William; Samsulbhari Mohd Nasir; Kharhan Bin Haji Jait (Human Resource Management Academic Research Society (HRMARS), 2025)
The world of food and nutrition is a form of heritage deeply embedded in the culture of every ethnic group, representing the transmission of knowledge from one generation to the next. Each ethnicity expresses its unique characteristics through oral traditions and actions that shape cultural accomplishments. The Javanese community is particularly well-known for the deliciousness of its cuisine, which has become a popular choice not only among the Javanese themselves but also among people from other communities. Therefore, this study examines the intrinsic and extrinsic factors that contribute to the success of food businesses among the Javanese community in Kota Kinabalu, Sabah. This is a case study involving five Javanese participants in Kota Kinabalu who are actively engaged in the food business. The findings reveal that several intrinsic and extrinsic factors serve as motivating drivers that lead to the success of Javanese entrepreneurs in the food industry. The study also presents a new finding, highlighting that the success of the 4Ps of marketing, Product, Place, Price, and Promotion, must be supported by the value of honesty for a food business to continue growing and progressing. The implications of this study provide a new dimension of knowledge and offer practical contributions to enhancing indigenous entrepreneurship, particularly in the food retail business sector. The findings of this study are also useful to the government in advancing food-based entrepreneurship globally.